PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DAN SOFT SKILL GURU TERHADAP KINERJA GURU DI SEKOLAH DASAR GUGUS 16 PONDOK AREN TANGERANG SELATAN - Imronah Amelia, Iin; C. Kurniatun, Taufani; Warsihna, Jaka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify and examine the magnitude of the influence of principals’ transformational leadership and teachers’ soft skills on teacher performance in Cluster 16 of Pondok Aren. This study employed a quantitative approach using a questionnaire method to collect samples from the population of all teachers and principals in Cluster 16, Pondok Aren, South Tangerang. A total of 152 respondents were selected as the research sample using a probability sampling technique. Data were collected through questionnaires based on a Likert scale. The data analysis technique used was Smart PLS with Structural Equation Modeling (SEM) analysis. The results of the hypothesis testing indicate that: (1) principals’ transformational leadership has a significant effect on teacher performance in elementary schools in Cluster 16, Pondok Aren, South Tangerang, with a p-value of 0.008 < 0.05; (2) teachers’ soft skills have a significant effect on teacher performance in elementary schools in Cluster 16, Pondok Aren, South Tangerang, with a p-value of 0.000 < 0.05; and (3) principals’ transformational leadership and teachers’ soft skills simultaneously have a significant effect on teacher performance in elementary schools in Cluster 16, Pondok Aren, South Tangerang, with a p-value of 0.000 < 0.05. The study concludes that principals’ transformational leadership and teachers’ soft skills significantly influence teacher performance in Cluster 16 of Pondok Aren.